Empowering and Disempowering Motivational Climates, Mediating Psychological Processes, and Future Intentions of Sport Participation - Castillo Jiménez, Nallely; López Walle, Jeanette M.; Tomás Marco, Inés; Tristán Rodríguez, José Leandro; Duda, Joan L.; Balaguer Solá, Isabel (Molecular Diversity Preservation International, 2022)
Based on the conceptual model of multidimensional and hierarchical motivational climate the objective of this study was to test two models. One model (M1) of total mediation, testing the mediating mechanisms that explain why the motivational climate affects intention of continuity or dropout. Specifically, we test the mediating role of satisfaction/frustration of basic psychological needs and self-determined motivation, in the relationship between the players’ perception of the empowering and disempowering climate created by the coach, and the intention of young soccer players to continue/dropout the sport practice. The second model (M2) of partial mediation, contributes to knowing the mechanisms that link the antecedent variables included in the model (perceived empowering and disempowering motivational climate) and the outcomes (intention of continuity or dropout in sport). A total of 381 young male soccer players between 12 and 14 years of age (M = 12.41, SD = 0.89), completed a questionnaire package tapping into the variables of interest: players’ perception of the motivational climate created by the coach (empowering and disempowering), satisfaction/thwarting of basic psychological needs, self-determined motivation and the intention to continue/dropout sports participation. The hypothesized model was tested using a structural equation model technique with latent variables. The results of the partial mediation model were satisfactory (χ2= 120.92; df = 68; RMSEA = 0.045; CFI = 0.968; TLI = 0.957) and showed that need satisfaction and self-determined motivation partially mediated the relationship between the perception of the empowering climate and the intention to continue. Moreover, need satisfaction showed a positive and significant relationship with the intention to continue sports participation. Additionally, need thwarting and self-determined motivation totally mediated the relationship between the perception of the disempowering climate and the intention to dropout. Furthermore, needs thwarting was positively and significantly related to the intention to dropout of sports participation. Findings point to the importance of fostering empowering climates and preventing the creation of disempowering climates in the grassroots football.